IS SELF-REGULATION A MYTH? CASE STUDY ON SPANISH GROUNDWATER USER ASSOCIATIONS AND THE ROLE OF HIGHER-LEVEL AUTHORITIES - Lopez-Gunn E.; Cortina L.M. (My University, 2006)
Self-regulation of groundwater users offers tremendous potential for effective groundwater management. The attributes of higher-level authorities that are more likely to facilitate the beneficial management of groundwater in economic, social and environmental terms are discussed. For this purpose, eight groundwater user associations in Spain have been compared. Factors that support institutional change were analyzed, namely: salience, common understanding, trust and reciprocity, autonomy, prior organizational experience and local leadership. These factors are complemented by features that strengthen actions by higher-level authorities that oversee self-regulation by water users (clear boundaries, legitimate recognition of appropriators, facilitating roles, trust in cross-scale linkages, clear division of responsibilities, institutional culture and co-management model choices). Self-regulation includes the creation of reflexive organizations that are capable of learning, provided first, the administration itself is modernized to meet the challenges of self-regulation, and second, that ‘regulatory capture’ is avoided by external organizations, ensuring that the regulator and the regulated are not so close in their relationship as to be detrimental to effectiveness.
Keywords: SELF-REGULATION; WATER USER ASSOCIATIONS; GROUNDWATER GOVERNANCE; SPAIN; SOCIOECONOMIC FACTORS